Novel Relations : Victorian Fiction and British Psychoanalysis - Christoff, Alicia Mireles (Book collections on Project MUSE., 2019)
Novel Relations engages twentieth-century post-Freudian British psychoanalysis in an unprecedented way: as literary theory. Placing the writing of figures like D.W. Winnicott, W.R. Bion, Michael and Enid Balint, Joan Riviere, Paula Heimann, and Betty Joseph in conversation with canonical Victorian fiction, Alicia Christoff reveals just how much object relations can teach us about how and why we read. These thinkers illustrate the ever-shifting impact our relations with others have on the psyche, and help us see how literary figures--characters, narrators, authors, and other readers--shape and structure us too. For Christoff, novels are charged relational fields. Closely reading novels by George Eliot and Thomas Hardy, Christoff shows that traditional understandings of Victorian fiction change when we fully recognize the object relations of reading. It is not by chance that British psychoanalysis illuminates underappreciated aspects of Victorian fiction so vibrantly: Victorian novels shaped modern psychoanalytic theories of psyche and relationality--including the eclipsing of empire and race in the construction of subject. Relational reading opens up both Victorian fiction and psychoanalysis to wider political and postcolonial dimensions, while prompting a closer engagement with work in such areas as critical race theory and gender and sexuality studies. The first book to examine at length the connections between British psychoanalysis and Victorian fiction, Novel Relations describes the impact of literary form on readers and on twentieth- and twenty-first-century theories of the subject.